The Effectiveness of Flashcard Vocabulary in Learning Foreign Language (English and Japanese) to Enhance the Speaking Skill for Beginner - Lulu Fahkrunisa; Reffy Ananda Rizki (Journal of Curriculum and Pedagogic Studies (JCPS), 2022)
This research is a class action research which conducted on students whose studying foreign languages such as English and Japanese. This research is descriptive qualitative research by using flash card vocabulary as a learning medium. The purpose of this study is to improve the students' ability to use the foreign language which they learn (English and Japanese). This study was carried out in two cycles, which is in every cycle have four meetings. Then, from the results of this research has been carried out, it is known that students' ability to speak using foreign languages before using the flash card vocabulary shows in below-average results, where only one student achieved a total score of 50 percent, and after using flashcard vocabulary learning media, the average showed that the ability to speak in foreign languages of all students increased by 70-80 percent. Keywords: English and Japanese Languages, Flashcard